PENGEMBANGAN MEDIA BUKU CERITA AUDIO VISUAL UNTUK MENINGKATKAN KEMAMPUAN SOSIAL EMOSIONAL ANAK 5-6 TAHUN - Maharani, Rini; Ali, Muhamad; Miranda, Dian (Universitas Tanjungpura, 2024)
This study aims to develop storybook using audio-visual to improve the social emotional abilities of children aged 5-6 years. This type of research is the ADDIE development model (Analyze, Design, Develop, Implement, and Evaluate). The subjects in this study were 14 children in TK Karya Nyata, Punggur Kecil, Kecamatan Sungai Kakap , Kabupaten Kubu Raya. The data obtained are in the form of quantitative and qualitative data so that the approach in this study is a mixed method. Based on the results of the t-test with a significance of 0.05%, it was obtained t count (7.3925) t table (2.160). This shows that there is a significant influence on the results of children's social emotional abilities before and after using audio visual story book. Based on the results of the study, it can be concluded that the audio visual story book can improve the social-emotional abilities of children aged 5-6 years in TK Karya Nyata, Desa Punggur Kecil, Kecamatan Sungai Kakap, Kabupaten Kubu Raya